Cytoskeleton of the nervous system - Nixon, Ralph A.; Yuan, Aidong; SpringerLink (Online service). (New York Springer, 2011)
Without a cytoskeleton, a neuron or glial cell would be a shapeless jelly mass unable to function in the milieu of the brain. If we are to understand neuronal cells function in health and disease, we must determine how the cytoskeleton forms and contributes to neural physiology and pathobiology. Cytoskeleton of the Nervous System provides a comprehensive, authoritative and up-to-date account of what we now know and what we want to know in the near future--about the functioning of the cytoskeleton of neuronal cells at the molecular level. In lively accounts, which are unafraid to address controversy, Cytoskeleton of the Nervous System introduces readers to the most sophisticated concepts and latest discoveries: from overexpression systems to knock-out models for specific cytoskeletal proteins, from continuous transport assays in vivo to live-cell imaging in primary neurons, and from factors regulating cytoskeleton behavior to the dysregulation of these processes leading to neurological disease.
Central Axonal Development and Pathology in Early Life -- Microtubules in the nervous system -- Tau phosphorylation -- Tau Pathology -- Tauopathy and brain aging -- Microtubule-associated protein 4 -- Structure of Neural Intermediate Filaments -- Alpha-internexin: the Fourth Subunit of Neurofilaments in the Mature CNS -- Peripherin Pathology -- Neurofilament cross-bridge: a structure associated specifically with the neurofilament among the intermediate filament family -- Neurofilament Transport -- Knockout models of neurofilament proteins -- Neurofilaments and Radial Growth: Deconstruction of a hypothesis through the construction of gene targeted mice -- Deregulation of Cytoskeletal Protein Phosphorylation and Neurodegeneration -- Neurofilaments in Aged Animals -- Neurofilament changes in Multiple Sclerosis -- Intermediate filament interactions in neurons -- Tropomyosins in Neuronal Morphogenesis and Development -- The Driving Machinery for Growth Cone Navigation -- Glial Fibrillary Acidic Protein: The intermediate filament protein of astrocytes -- Axonal Transport Mechanisms in Cytoskeleton Formation and Regulation -- Axonal transport and motor neuron disease -- In vivo imaging of axonal transport in aging and Alzheimer's disease -- Regulation of Cytoskeletal Composition in Neurons: Transcriptional and Post-transcriptional Control in Development, Regeneration, and Disease -- Crosstalks between myelinating cells and the axonal cytoskeleton -- Topographic regulation of neuronal intermediate filament proteins by phosphorylation: In health and disease -- Cytoskeleton, axonal transport, and the mechanisms of axonal neuropathy -- Effects of Insulin on Tau and Neurofilament -- Ethanol effects on the cytoskeleton of nerve tissue cells.
Electronic reproduction.
Keywords: Cytoskeleton; Nervous system -- Cytopathology; Cytoskeleton -- Physiology; Nervous system physiological phenomena; Axonal transport -- Physiology; Nervous system -- Growth & development; Neurons -- Cytology; Electronic books